Multiple brain abscess from dental origin: Case report and literature review - Azenha, Marcelo Rodrigues [UNESP]; Homsi, Guilherme; Garcia Júnior, Idelmo Rangel [UNESP] (Springer Nature, 2012)
Background: Brain abscess of dental origin is a rare situation and deserves attention due to its high mortality rate even when adequate treatment is done. Few reports are available when dental origin is the main cause of this infection. Case report: We present the case of a 70-year-old man diagnosed with cerebral abscess caused by apical lesions located at superior and inferior teeth. The three lesions containing pus were drained from anterior and posterior brain region and the laboratory evaluation revealed the presence of Streptococcus viridians and Bacteroides. Postoperative period was uneventful with excellent recovery after 1 year of surgery. Final diagnosis was able to be done due to excellent image exams availability like computer tomography and magnetic resonance using diffusion and perfusion techniques. Discussion: The early detection of this pathology with the correct diagnosis essential to give the patient the best treatment including antimicrobial drugs and drainage is of extreme importance. © 2011 Springer-Verlag.
Keywords: Brain abscess; Dental infection; Infection; Surgery